Network Pharmacology-based Analysis of Chemical Compounds from Roselle (Hibiscus sabdariffa) and Garcinia mangostana L. for Anti-hypercholesterolemic Activity - Diah Dwi Darma; Habiburrahman Zulfikri; Heri Setiawan (Sarana Ilmu Indonesia (Salnesia), 2026)
Roselle tea (Hibiscus sabdariffa) is widely used as a traditional remedy for hypertension and hyperlipidemia, while mangosteen (Garcinia mangostana L.) is known to contain secondary metabolites with potential efficacy in the management of hypercholesterolemia. This study aimed to investigate the activity and mechanism of action of the combination of both plants as anti-hypercholesterolemic agents through a Network Pharmacology-based analysis. Active compound identification was performed using the KNApSAcK Family database, ADMET analysis was conducted using the pkCSM and ProTox servers, and protein-protein interactions were analyzed using Cytoscape and STRING. Mechanisms of action were further elucidated through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) Pathwayy analyses using ShinyGO 0.77. The results indicated that β-sitosterol from mangosteen occupied a central role in the anti-hypercholesterolemic interaction network, as indicated by the highest degree value (12.6658), while β-sitosterol, 3,4-dihydroxybenzoic acid, and quercetin from roselle were found to regulate key target genes including ABCA1, APOA1, BAX, BCL2, CASP3, and CD36. These genes were involved in lipid metabolism and the pathophysiology of atherosclerosis, which represents a primary complication of hypercholesterolemia. Further research is warranted to validate the efficacy of the combination of extracts or active compounds from both plants, both in vitro and in vivo.